Coliform bacteria as components in biofilm of manure effluents - L. V. Pilip; N. V. Syrchina; T. Ya. Ashikhmina; E. P. Kolevatykh (Юг России: экология, развитие, 2023)
Aim. To study the intraspecific diversity of coliform bacteria represented in microbial communities in biofilms of manure effluents (ME), as well as to evaluate the effect of chemical reagents on the composition of microbial consortia and some properties of bacteria of the genus Escherichia.Material and Methods. Biofilms of ME were obtained under laboratory conditions and their qualitative and quantitative microbial composition studied. H2SO4 and NaOCl solutions were used for entry into ME. The composition of the microbiota was determined by the method of inoculation on nutrient media.Results. The dominant groups of microorganisms in biofilms of ME were obligate and facultative anaerobic bacteria of the genera Clostridium, Bacteroides and Escherichia. The genus Escherichia is represented by E. coli, E. fergusonii, E. hermannii (Atlantibacter hermannii), E. blattae (Shimwellia blattae), E. coli inactive and E. vulneris with varying biochemical activity. Escherichia fergusonii, Escherichia coli inactive and Escherichia vulneris have increased colonization potential, which contributes to the survival of bacterial populations in the bacterial consortium. Bacteria of the genus Escherichia are able to form associations with the facultative anaerobe Proteus vulgaris and the yeast Rhodotorula glutinis. The significant resistance of E. coli to the effects of chemical reagents used to neutralize and eliminate the smell of ME (H2SO4 to pH 5.5±0.1; introduction of 12.5 mg/l of active chlorine in NaOCl) was revealed. ME treatment did not lead to the complete death of E. coli. However, it reduced the concentration by 2 orders of magnitude. The use of these chemicals can reduce the total volume of gases released by 30–40% and reduce the intensity of unpleasant u.Conclusions. The results obtained can find practical application in the development of formulations of biological products to reduce odour and improve the efficiency of rational disposal of animal by-products.